Eucalypts in India - Chaturvedi, A. N. (Indian Forester, 1976)
This paper begins with a brief history of Eucalyptus trials in India and then describes in detail the planting technique, genetical status and statistics of growth and yield of Eucalyptus hybrid-the most extensively planted Eucalyptus species in India today. Based on the data of several permanent and temporary sample plots results of following studies carried out by the author are presented. (i) Volume and weight equations correlating volume and weight with diameter and height of trees. (ii) Stand volume equations correlating stand volume per hectare with basal area and top height. (iii) Regression model correlating M.A.I. with age stand and site characteristics.